(untitled) (OCEM Journal of Management, Technology & Social Sciences, 2023)
The primary objective of this study was to evaluate the different models of the mixed methods approach along with research problems, questions, and data analysis techniques and to review its overall methodology applied to collect data in a selected educational article. A mixed methods approach is a newly emerged research design of this 21st century where both quantitative and qualitative data can be collected one at a time. This study was based on the review of different articles, books, cases, magazines, and newspapers connecting with the mixed methods approach. The key focus of this study was to introduce the mixed methods approach, quantitative and qualitative approaches, evaluate the theoretical strengths and weaknesses of the mixed methods approach, and explicit meaning of both qualitative and quantitative design and its applications in the different fields of research studies. The results indicate that the study has covered different aspects of the mixed methods approach along with the theoretical weaknesses of the mixed methods approach. The results have also focused on both quantitative and qualitative research approaches along with the mixed methods approach and different designs of the mixed methods approach. The results further indicate that the core designs of the mixed methods approach are contemporary development and expansion designs, the validity and reliability of the mixed methods approach, the generalization of research outcomes, and statistical generalization. It was indicated that the key findings and discussions were also focused on while reviewing different journals and online documents. The results suggest that factors affecting teacher retention and attrition intention were based on the high workload and unsupportive colleagues and administration, which are similar within China, Nepal, India, and Sri Lanka. The results show that approximately 42% of the teachers reported being highly stressed in China; the same scenario has also occurred in the Nepalese context. The implications of this study would be beneficial to young researchers, students, college teachers and master-level students to foreground the knowledge in the mixed methods approach.